PENGELOLAAN PROGRAM ADIWIYATA DI SMP NEGERI 2 PANGKALAN KERINCI KABUPATEN PELALAWAN - ROMITA DASRA; ZULFAN SAAM; ISJONI ISJONI (Universitas Riau, 2017)
Management of Adiwiyata Programme consist of four aspect are environmentpolicy, environment curriculum, activity of environtment based participative, and facilitiessupported environmentally friendly. This research aims to analysed management of AdiwiyataProgramme and descripted of planning, organizing, actuating and controlling Adiwiyata programmeat State Junior High School 2 Pangkalan Kerinci The Distric Pelalawan. The qualitative reseachaproach and type of the reseach is a descriptive analytic study. For data collection tecniques areinterviews, observation and documentation. From the analysis of the data in State Junior HighSchool 2 Pangkalan Kerinci obtained results, (1) management of environment policy has beenmanaging trought revision the vision and mission of the school and the allocation of funds forAdiwiyata Programme, (2) management of environment curriculum has been managing troughtcurriculum integrated, (3) management of environment activities based participative has beenmanaging through various environment action like a “Sabtu Bersih Programme,” invite studentto participate trought extracuricular activities like PLH, KIR and Scouting, also ensure schoolpartnerships with “Puskesmas” to environment instigation, (4) management of facilities thesupporting environmentally friendly like provision of disposal waste, provision of coposting, andschool gardens. Improving the quality of facilities and infrastructures are improving the qualityof healthy canteen service and friendly environment like to canteen not use plastical stuff tofood packing, used of electricity, water and “ATK” eficiently, improving management of schoolsanitation. From some of research are found that the management of Adiwiyata programmehave optimal.